Analysis of the current usage of resuscitative endovascular balloon occlusion of the aorta (REBOA) in pediatric trauma patients: a retrospective observational study from the American College of Surgeons–Trauma Quality Improvement Program databases - Ling-wei Kuo; Chih-Yuan Fu; Chien-An Liao; Chien-Hung Liao; Chi-Tung Cheng; Jen-Fu Huang; Chi-Po Hsu; Chia-Cheng Wang (Trauma Surgery & Acute Care Open, 2024)
Background Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been an established life-saving procedure for adult trauma patients, but the evidence for its use in pediatric patients is still under question. The purpose of this study was to examine the outcome of REBOA in pediatric patients.Methods We retrospectively analyzed observational cohort data from the American College of Surgeons–Trauma Quality Improvement Program from 2017 to 2019. We analyzed 183 506 trauma patients aged 7–18, and 111 patients were matched by propensity score analysis. Basic demographics, injury severity, trauma type, and clinical outcomes of the patients receiving REBOA and those not receiving REBOA were compared. In the REBOA patients, a subgroup analysis was performed to evaluate the potential influence of age and body weight on the outcomes of REBOA.Results After the pretreatment factors were balanced for the REBOA and no-REBOA groups, the patients in the REBOA group had more transfused packed red blood cells within the first 4 hours (3250 mL vs. 600 mL, p<0.001), and the mortality rate was higher in the REBOA group, but it did not reach statistical significance (56.8% vs. 36.5%, p=0.067). No significant difference was detected regarding in-hospital complications. In the subgroup analysis of the patients who received REBOA, we discovered no significant difference in mortality and complications between the subgroups when compared by age (>15 years old/≤15 years old) or weight (>58 kg or ≤58 kg).Conclusions Pediatric trauma patients who received REBOA were not significantly associated with an increased risk of mortality when compared with no-REBOA patients with matched basic demographics and pretreatment factors. Younger age and lighter body weight did not seem to influence the outcomes of REBOA regarding survival and complications.Level of evidence Level III